Effects of medium fluid cavitation on fluctuation characteristics of magnetic fluid seal interface in agricultural centrifugal pump - Li, Zhenggui; Li, Wangxu; Wang, Qifan; Xiang, Ru; Cheng, Jie; Han, Wei; Yan, Zhaoqiang (International Journal of Agricultural and Biological Engineering, 2021)
The fluctuation law of magnetic fluid seal interface of an agricultural centrifugal pump is theoretically unknown; the pressure and velocity fluctuations are crucial factors that cause interface fluctuation. In this study, the pressure and velocity fluctuations of the sealing interface on an agricultural centrifugal pump during cavitation were investigated based on the methods of Ansys CFX numerical calculation and experimental verification. The results demonstrated that at the same flow rate, the pressure fluctuation amplitude of the sealing interface decreased gradually from the shaft surface to the bottom of the polar tooth. At different flow rates, the amplitude of the pressure fluctuation decreased with an increase in the flow rate. The cavitation of the medium aggravated the impact and water hammer of the liquid, leading to the occurrence of the jitter phenomenon in the sealing interface to accelerate the fluctuation frequency of the axial velocity of the sealing liquid, which accelerated the emulsification of the magnetic fluid. This law can provide a reference for the design of magnetic fluid sealing devices for agricultural centrifugal pumps. Keywords: centrifugal pump, magnetic liquid sealing device, medium cavitation, interface fluctuations DOI: 10.25165/j.ijabe.20211406.6718 Citation: Li Z G, Li W X, Wang Q F, Xiang R, Cheng J, Han W, et al. Effects of medium fluid cavitation on fluctuation characteristics of magnetic fluid seal interface in agricultural centrifugal pump. Int J Agric & Biol Eng, 2021; 14(6): 85–92.